Child self-report and child-parent agreement regarding health-related quality of life under COVID-19 lockdown in the French Grand Est area. (April 2023) - Bourion-Bédès, Stéphanie; Rousseau, Hélène; Batt, Martine; Tarquinio, Pascale; Lebreuilly, Romain; Sorsana, Christine; Legrand, Karine; Tarquinio, Cyril; Baumann, Cédric
Highlights: Compared to normative European scores in a previous reference study, the children and adolescents had lower HRQoL scores during the lockdown. Moderate to good levels of agreement between the children's and parents' responses were found for all KIDSCREEN-27 dimensions. Agreement between children and parents is worse among younger children in the psychological dimension. Abstract: Nearly 1.6 billion of children and young people in more than 190 countries have been affected by school closures under the first lockdown due to the coronavirus disease. This study aimed to investigate child-reported and parent-rated health-related quality of life among 8- to 18-year-olds and the agreement between the children's assessments and those of their parents during lockdown. A cross-sectional study was conducted among French children living in the Grand Est area. An online survey was used to collect data on the children's sociodemographics, living environments, education and HRQoL. The latter was assessed with KIDSCREEN-27, which consists of five domains. Sex and age differences in parent ratings and child-reported data were analyzed using Mann-Whitney tests. Child-parent agreement was analyzed using the intraclass correlation coefficient (ICC). In total, 471 child-parent pairs from 341 households were included. Compared to European norms, children scored lower on all dimensions during the first lockdown: physical well-being (45.9/49.94 EU), psychological well-being (48.8/49.77 EU), parent relations and autonomy (47.7/49.99 EU), social support and peers (36.4/49.94 EU) and school (48.2/50 EU). Significant child-reported sex and age differences were identified for both psychological and physical well-being dimensions. Moderate to good agreement existed between children's and parents' ratings on all KIDSCREEN dimensions (ICC ranged from 0.60 to 0.76). The study suggests the need to focus on children's social support and peers during epidemics and to consider the children's self-reported HRQoL. Additional research should be conducted to identify ways of minimizing the gap between mental health needs and the services available and to help more children maintain their physical and mental health during the current crisis.